Relevansi Hukum Alam Rasional dalam Interpretasi Pancasila Sebagai Sumber Dari Segala Sumber Hukum - A, Annisa; Wahdah, Azzhara Nikita; Tambunan, Joy Catherine Carina; Rubianti, Vaganti Safa Sukma; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Pancasila, as the source of all sources of law, has a central position in Indonesia's national legal system. However, the main challenge faced is how to translate the abstract values of Pancasila into concrete and operational positive legal norms. This article examines the relevance of the concept of rational natural law as a philosophical approach in interpreting Pancasila contextually in the formation of legislation. Rational natural law emphasizes the importance of reason and universal moral values as the basis for the formation of law, so that the law is not only formally valid, but also substantially fair. In the Indonesian context, Pancasila values such as social justice, fair and civilized humanity, and deliberation are consistent with the principles of rational natural law. Through this approach, Pancasila values can be transformed into legal principles that are relevant to the needs of modern society, such as the principles of proportionality, balance of interests, and protection of natural rights. This study uses a normative juridical method with a legislative approach and qualitative analysis of regulations and court decisions that reflect the application of rational natural law principles. The results of the study show that the interpretation of rational natural law in relation to Pancasila acts as a bridge between philosophical values and positive legal norms, as well as a filter against global influences so that national law continues to reflect the nation's identity.